2022
DOI: 10.1155/2022/7243399
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Plasma Pentraxin 3 and Serum Amyloid P Levels and Disease Activity in Ankylosing Spondylitis

Abstract: Background. In clinical practice, it is hard to judge the level of disease activity in some patients with ankylosing spondylitis (AS) who have low traditional acute phase reactant values such as erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) but have considerable pain and inflammation. The aim of this study is to investigate plasma pentraxin 3 (PTX3) and serum amyloid P (SAP) levels in patients with AS who had normal ESR and CRP but high disease activity. Methods. 100 AS patients and 100 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…PTX-3 levels were also not correlated with disease activity. Although there are few studies in the literature examining PTX-3 levels and disease activity, to the best of our knowledge, this is the first study to compare PTX-3 with serum IL-17 and IL-23 levels, as well as nr-AxSpA and r-AxSpA groups [14][15][16].…”
Section: Axspa (N = 50)mentioning
confidence: 99%
See 1 more Smart Citation
“…PTX-3 levels were also not correlated with disease activity. Although there are few studies in the literature examining PTX-3 levels and disease activity, to the best of our knowledge, this is the first study to compare PTX-3 with serum IL-17 and IL-23 levels, as well as nr-AxSpA and r-AxSpA groups [14][15][16].…”
Section: Axspa (N = 50)mentioning
confidence: 99%
“…Ozdemirel et al [15] examined plasma PTX-3 and serum amyloid P (SAP) levels in 100 AS patients and reported that AS patients had higher PTX-3 and SAP levels than the healthy group. Similar to our study, they found no correlation between PTX-3 levels and disease activity.…”
Section: Axspa (N = 50)mentioning
confidence: 99%
“…Pentraxin 3 is a long pentraxin overexpressed during the acute-phase response, playing significant roles in the innate immune response and inflammation, as well as in tissue damage and remodeling. Its direct implications in axSpA and many other rheumatic disorders have been extensively studied [ 77 ]; unfortunately, some studies have shown no association with disease activity and acute inflammation in axSpA [ 56 , 78 ].…”
Section: Systemic Markers Of Inflammationmentioning
confidence: 99%
“…In AS patients, the inflammatory response is often accompanied by aberrant production of multiple cytokines. For example, tumour necrosis factor-alpha (TNFa), interleukin-1 beta (IL-1b) and interleukin-17 .Such irregular production and activation of these inflammatory factors can lead to joint and spinal inflammation, pain and tissue damage (5)(6)(7). Therapeutic approaches targeting these inflammatory factors, such as the use of biological agents to inhibit TNFa, have gained widespread acceptance in the treatment of AS (8).…”
Section: Introductionmentioning
confidence: 99%